Perspectives of Electricity Storage in Polymer Capacitors - Dudic, Duško (Journal of Research Updates in Polymer Science, 2021)
The price and environmental aspects of electricity storage significantly affect the application of green technologies. The electrochemical batteries are currently the best choice for storing electricity for most industrial needs and products. Polymer capacitors show very low energy density compared to conventional batteries and therefore cannot be widely used for electricity disposal. At the same time, all other features of polymer capacitors that characterize battery systems are ideal. After a brief comparison of the basic properties of electrochemical and physical batteries, this paper presents the influence of electron trapping on the energy density of a polyethylene capacitor. The presented results indicate that the phenomenon of electron trapping in polymers can increase the energy deposit of polymer capacitors.